Prototype Aplikasi Rekomendasi Rekruitmen Karyawan Start-Up Pemula Menggunakan Metode Multi Attribute Utility Theory - Maulana, Danis; Brillyanto, Muhammad Haffid Indra; Akseptori, Ristanti; Suhardjito, Gaguk; Rachman, Farizi (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2023)
Research aim : The purpose of this study is to present a solution in the form of a web-based system with the Multi Attribute Utility Theory (MAUT) method approach to provide convenience in the employee selection process at CV. Bee Digital Prestasi Nusantara. Design/Methode/Approach : The Multi Attribute Utility Theory method approach provides a solution in the form of recommendations for the final results of the selection process which is carried out by conducting an assessment through several alternatives and sub-alternatives multiplied by the weight that has been determined by the company. The method approach was divided into several stages: (1) Submissions and Tests (2) Calculation of Values, Criteria and Weights (3) Ranking. Research Finding: The application of the MAUT method can provide effective decisions on the recruitment of prospective employees accepted by the company. The experimental results from the research showed that using MAUT method is able to speed up the recruitment process and can quickly determine prospective employees who match the company's criteria compared to conventional methods. Theoretical contribution/Originality : This research result showed that theoretically, MAUT method supports the employee selection process Practitionel/Policy implication : The practical implication is that the attributes used in the selection process support the company in getting employees that match their needs Research limitation : This method has limitations, namely the range of values is still static. So, it needs improvement in the next research. Keyword: Recruitment, Multi Attribute Utility Theory, Prototype, Agile